High prescription rate of oral glucocorticoids in children and adults: A retrospective cohort study from Western Sweden. (12th November 2019) - Einarsdottir, Margret J.; Ekman, Per; Trimpou, Penelope; Olsson, Daniel S.; Johannsson, Gudmundur; Ragnarsson, Oskar
Abstract: Objective: Glucocorticoids (GCs) are a cornerstone in treating various common and uncommon diseases. The aim of this study was to estimate the prevalence of GC use in terms of doses associated with risk of tertiary adrenal insufficiency in adults and children, and treatment indications. Methods: This was a retrospective cohort study. Information on dispensed prescriptions was obtained from the Swedish Prescribed Drug Register. Patients with prescriptions of prednisolone (or equivalent dose of other GCs) ≥5 mg daily for ≥21 days between 2007 and 2014 were included. Information on concurrent diseases was obtained from the Swedish National Patient Register and the Västra Götaland Regional Healthcare Database. Results: Of 1 585 335 inhabitants in Västra Götaland County, 223 211 were included in the study (women 55.6%). Mean age was 48 ± 24 years. Period prevalence of oral GC use during the 8‐year study period was 14.1%. The highest prevalence (27.4%) was in men aged 80‐89 years and lowest (7.5%) in men 10‐19 years of age. The period prevalence in children 0‐9 years of age was 10.6%. COPD and asthma were the most common indications for treatment (17.2%) followed by allergy (12.5%) and malignant neoplasms (11.5%). Allergy was the most frequent indication (20.5%) in children and adolescents. Conclusion: Between 2007 and 2014, every seventh inhabitant in western Sweden received a GC prescription at doses associated with risk of developing tertiary adrenal insufficiency. These findings illustrate the importance of awareness of the potential development of tertiary adrenal insufficiency in both paediatric and adult patients.